(untitled) (Journal of Foreign Language Studies, 2024)
Interactive Whiteboard (IWB), a new technology in education that offers strong interactive features and effectively supports teaching and learning activities, has been widely used in many countries around the world over the past decade. In Vietnam, IWB is less explored due to the associated high cost and the need for other accessories such as projector, computer and speakers. Some schools are equipped with IWB but only limited features of IWB have been utilized. Thus, the aim of this paper is to provide readers with a succinct description of IWB, and to make recommendations on how to maximize the usage potential of IWB in teaching and learning foreign languages.